Pengaruh Gender Terhadap Kesadaran Politik Siswa Sekolah Menengah Atas - Patmisari, Patmisari; Gafur, Abdul (Universitas Negeri Malang, 2019)
This article aims to describe the effect of gender differences in the political awareness of high school students as a novice voter. The study method uses a correlational research design using a quantitative approach. The analysis used was independent samples T-test using SPSS 21. Data collection instruments used a questionnaire distributed to research samples. The sample is 245 students consisting of 128 female students and 117 male students. The results of the study showed differences in the level of political awareness between male and female students, male students had higher political awareness than female students. There is a positive and significant gender influence on the political awareness of high school students.